Hubungan Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Sekretariat Deputi Kemenparekraf RI - Nur Azizah; Ani Wijayanti; Dhuha Safria (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This study aims to determine the relationship between Leadership Style and Work Motivation simultaneously on Employee Performance of the Deputy Secretariat of the Ministry of Tourism and Creative Economy of the Republic of Indonesia which is an agency for the protection of tourism and the creative economy which has the duties and functions of preparing strategic plans, evaluating performance, and establishing cooperation with various related parties to achieving goals and development in the field of tourism. This research method uses a statistical quantitative method and is measured using the Statistical for the Social Science Package (SPSS) Version 23. The sample in this study is a saturated sample of 50 employees of the RI Ministry of Tourism and Creative Economy Deputy Secretariat. through instrument testing using the t test and f test to prove the hypothesis. The results of the study show that the relationship between leadership style and work motivation on employee performance is simultaneously positive and significant. Leaders in the strategic policy deputy secretariat work unit need to maintain work motivation and apply a more effective and appropriate leadership style, so that employee performance will get better.